Collected minor works and teachings of the Third Khamssprul Ṅag-dbaṅ-kun-dgaʼ-bstan-ʼdzin - Ṅag-dbaṅ-kun-dgaʼ-bstan-ʼdzin, Khams-sprul III, 1680-1728 (Collected works of the successive embodiments of the Khams-sprul series ;, 1976)
Collected writings, largely on Lamaist practice, of a scholar of the Drukpa Kargyudpa sect.